Evaluation of the Effect of Light Color on Albumins and Globulins Content During Bean Germination - Victor Manuel Rivera Aguilar; José Pedraza-Chaverri; David Julian Arias-Chávez; Ruth Jaimez; Edgar Flores-Soto; Isaías E. Garduño; Fernando S. Chiwo; Celia Sánchez Pérez; Ana del Carmen Susunaga Notario (Foods)
The effect of different light colors on the concentration of albumins and globulins during black bean (Phaseolus vulgaris L.) germination was evaluated with an RGB LED lighting system. This study aimed to determine how light of different spectral composition influences protein content across different germination stages. Black bean seeds were germinated under six different LED light sources (red, green, blue, white, violet, and cyan), and protein fractions were quantified by Bradford’s method. The results showed that blue and cyan light increased the concentration of albumins. Blue, white, and cyan light for globulins increased the concentration compared to germination under solar conditions for both fractions. The positive correlation between these protein fractions under specific wavelengths suggests a metabolic adaptation to light exposure. These findings highlight the potential of controlled lighting conditions to enhance the nutritional quality of germinated beans, supporting their application as functional food ingredients. Additionally, this study underscores the importance of photobiological modulation in seed germination, opening new possibilities for optimizing plant-based protein sources. Future research could explore the mechanisms behind these protein variations and their implications for food production and nutrition.